PEMBELAJARAN VIDEO MENGGUNAKAN APLIKASI CANVA PADA MATA PELAJARAN SKI KELAS V MI HIJRIYAH II PALEMBANG - Jauhara; Middya Boty; Amir Hamzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of instructional media can assist teachers in improving the quality of learning. The presence of instructional media also helps students develop a shared understanding of the material being taught. Nearly all human activities today are connected to science and technology (abbreviated as IPTEK in Indonesian). Science and technology can also be utilized in the field of education. One example of this utilization is the use of video media. Video media can be developed by educators using the Canva application. This study aims to explore the development of video-based instructional media using the Canva application for the Islamic Cultural History (SKI) subject in Grade 5 at MI Hijriyah II Palembang. The research method is a development study using the ADDIE development model. The sample in this study consists of class 5B, with a total of 34 students. The data analysis techniques used are validity analysis and practicality analysis. Data validity was tested through language validation, content validation, and media validation. The results of the study show that the process of developing video media using the Canva application through the ADDIE stages was implemented successfully according to plan. In terms of validity, the media falls into the